2020
DOI: 10.1155/2020/9083264
|View full text |Cite
|
Sign up to set email alerts
|

Early Pregnancy Screening for Women at High-Risk of GDM Results in Reduced Neonatal Morbidity and Similar Maternal Outcomes to Routine Screening

Abstract: The Australasian Diabetes in Pregnancy Society recommends screening high-risk women for gestational diabetes mellitus (GDM) before 24 weeks gestation, under the assumption that an earlier diagnosis and opportunity to achieve normoglycemia will minimize adverse outcomes. However, little evidence exists for this recommendation. The study objective was to compare the pregnancy outcomes of high-risk women diagnosed with GDM before 24 weeks gestation and routinely diagnosed women after 24 weeks gestation. A retrosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
2
21
0
1
Order By: Relevance
“…An Australian study demonstrated also that early diagnosis and intervention had no effect on pregnancy outcomes [ 21 ]. This was confirmed by a recent Australian study showing no differences in pregnancy outcomes between early-onset GDM and late-onset GDM [ 30 ].…”
Section: Resultssupporting
confidence: 77%
See 2 more Smart Citations
“…An Australian study demonstrated also that early diagnosis and intervention had no effect on pregnancy outcomes [ 21 ]. This was confirmed by a recent Australian study showing no differences in pregnancy outcomes between early-onset GDM and late-onset GDM [ 30 ].…”
Section: Resultssupporting
confidence: 77%
“…In general, most studies show that women with early GDM are at high risk for adverse pregnancy outcomes but treatment of GDM early in pregnancy compared to later in pregnancy does not always translate into improved outcomes. Seven studies reported an improved pregnancy outcome by treatment of early-onset GDM [ 7 , 9 , 10 , 29 , 30 , 31 , 34 ]. Barahona et al [ 9 ] showed that diagnosing GDM early in pregnancy is a predictor of adverse maternal and neonatal outcomes, such as pregnancy-induced hypertension, insulin treatment during pregnancy, preterm birth, hyperbilirubinemia and perinatal mortality.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is some evidence in support of a reduction in neonatal morbidity by achieving normoglycemia earlier in pregnancy with the adoption of early screening. For most healthy women, there is a lack of evidence linking early screening to improvements in neonatal outcomes [ 49 ]. However, high risk women are more likely to benefit from an early diagnosis of GDM.…”
Section: The Metabolomic Profile Of Gdm: a Review Of The Literaturementioning
confidence: 99%
“…However, high risk women are more likely to benefit from an early diagnosis of GDM. In a retrospective cohort study performed by Clarke et al [ 49 ], women with an “early GDM” diagnosis (at an average of 17 weeks’ gestation) had better composite neonatal outcomes than their later-diagnosed peers, despite arguably representing a higher-risk cohort. The authors suggest that this may have resulted from earlier intervention and point to this approximate gestation as a beneficial screening point, as interventions can be made prior to the development of a functional fetal endocrine pancreas [ 50 ].…”
Section: The Metabolomic Profile Of Gdm: a Review Of The Literaturementioning
confidence: 99%